PKM Pemanfaatan Daur Ulang Sampah Non-Organik Berbasis Ecobrick dalam Meningkatkan Ekonomi dan Kreativitas Santri Pondok Pesantren Nurul Jadid - Moh. Idil Ghufron; Siti Maryam; Sri Nurul Ulif Al Inayah; Fitria Fitria; Faizatul Aliyah; Yunita Nurmelinda; Sulis Nada (Universitas Nurul Jadid, 2021)
Garbage is an item deemed unused and disposed of by the previous owner/user, but for some people, it can still be used if it is managed with the right procedures. However, non-organic waste is often considered as environmental pollution due to industry and households. Therefore, this student service activity is to make use of non-organic waste to be useful by making it creative to deal with scattered garbage. The method of counseling and training for santri in the Al-Mawaddah area on how to make creativity such as flower pots and flowers from non-organic waste. The result obtained from this activity were: a) considerable enthusiasm from the students for the material they had been given, and b)increased knowledge of the students on the use of non-organic waste as a material for creativity.